1993
DOI: 10.1091/mbc.4.5.541
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fusion of endocytic vesicles is inhibited by cyclin A-cdc2 kinase.

Abstract: Receptor-mediated endocytosis and recycling are inhibited in mitotic mammalian cells, and previous studies have shown that inhibition of endocytic vesicle fusion in vitro occurs via cyclin B-cdc2 kinase. To test for the ability of cyclin A-cdc2 kinase to inhibit endocytic vesicle fusion, we employed recombinant cyclin A proteins. Addition of cyclin A to interphase extracts activated a histone kinase and markedly reduced the efficiency of endocytic vesicle fusion. By a number of criteria, inhibition of fusion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 80 publications
(89 reference statements)
1
19
0
Order By: Relevance
“…Inhibition of vesicle fusion is consistent with the observed general cessation of exocytic and endocytic transport during M-phase [10]. Work on endocytosis suggests that the inhibited step in the transport event is the fusion of vesicles with their target membrane [32,33]. In the case of the Golgi apparatus, inhibition of vesicle fusion would, of course, result in the accumulation of COP I vesicles in the vicinity of Golgi stacks.…”
Section: Cop I-dependent Disassemblysupporting
confidence: 76%
“…Inhibition of vesicle fusion is consistent with the observed general cessation of exocytic and endocytic transport during M-phase [10]. Work on endocytosis suggests that the inhibited step in the transport event is the fusion of vesicles with their target membrane [32,33]. In the case of the Golgi apparatus, inhibition of vesicle fusion would, of course, result in the accumulation of COP I vesicles in the vicinity of Golgi stacks.…”
Section: Cop I-dependent Disassemblysupporting
confidence: 76%
“…Cyclin A2 associated H1 kinase activity has been reported in the endosomal as well as ER fractions of rat liver cells and is increased in vivo during liver regeneration (Castro et al, 1994;Verges et al, 1997). It has been suggested that the kinase activity associated with cytosolic cyclin A2 might be implicated in the inhibition of in vitro intra-Golgi transport (Stuart et al, 1993;Mackay et al, 1993) and in the inhibition of the in vitro fusion of endocytic vesicles (Woodman et al, 1993), in contrast with previous reports (Thomas et al, 1992). The actual implications of these ®ndings for cell cycle progression have however not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies demonstrated that uptake of fluorescent dextran ceases during mitosis and also confirmed the timing of shutdown to be in early prophase (7). Many other studies went on to confirm and further develop the theory of mitotic shutdown of endocytosis, showing that it is temporary and resumes in telophase (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The reason for shutdown is unclear (18,19), but one recent idea is that "moonlighting" functions for endocytic proteins during mitosis may contribute to the inhibition (20,21).…”
mentioning
confidence: 96%